Implementasi Prosedur, Peraturan dan Konsekuensi Kelas Untuk Meningkatkan Kedisiplinan Siswa Kelas 8 - Hans Vindra Christian Sanjaya; Meicky Shoreamanis Panggabean (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Discipline is important in learning process as it could affect the success of learning process. Therefore, students should be responsible for their own behavior and keep the class conducive. Unfortunately, based on the researcher’s observation in grade VIII at a private school, the students had disciplinary problems. They came late to class, made noises when the teacher was explaining, and slept during class. Based on theories and journals, the researcher decided to implement classroom procedures, rules, and consequences. The purposes of this research were to know whether and how the implementation of the method can improve students’ discipline. The research method used was Pelton’s Model of Classroom Action Research (CAR). The subjects of research were 30 students from class VIII B. The research was conducted from August 14th to October 23rd, 2018. The instruments used were observation checklist forms, mentor’s feedback and researcher journal reflection that were analyzed by using simple statistics. Data analysis results showed that the average of indicator percentage of students' discipline improved 13% from 70% in Issue Identification to 83% Plan activation based on mentor’s observation after the implementation of the method. As conclusion, the implementation of classroom procedures, rules, and consequences could improve grade VIII students’ discipline by implementing all indicators of the method, which are: created a few rules, told the reason for each rule, created reasonable and logical consequences, explained procedures, rules, and consequences clearly, rehearsed procedures, reinforced correct procedures, and be consistent in implementing procedures, rules, and consequences.